The effect of transformational leadership on innovative work behaviour: The mediating role of knowledge sharing in Saudi Telecommunication Company - Almassri, Mohanad Issa (2025)
In the context of an increasingly competitive telecommunications industry, leaders at Saudi Telecommunication Company (STC) face the critical challenge of developing a workforce that is both innovative and performance-driven to sustain long-term competitive advantage. This study investigates the impact of transformational leadership dimensions namely (idealized influence behaviour, idealized influence attributed, inspirational motivation, individual consideration and intellectual stimulation) on innovative work behaviour (IWB), with a particular focus on the mediating role of knowledge sharing (KS). A quantitative research design was employed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach to examine the relationships among variables. The unit of analysis was individual employees at Saudi Telecommunication Company (STC). Using a random sampling technique, 310 online questionnaires were distributed to Saudi Telecommunication Company (STC) employees in Saudi Arabia, yielding a high response rate of 89.5%. The findings reveal that all dimensions of transformational leadership positively influence innovative work behaviour (IWB). Moreover, knowledge sharing (KS) was found to significantly mediate the relationship between transformational leadership and innovative work behaviour (IWB), highlighting its critical role as a mechanism through which leadership fosters innovation. This study concludes that innovative work behaviour (IWB), is enhanced when leaders encourage employees to think critically, take initiative, and adopt creative approaches to their tasks and challenges. The findings indicate that, to foster higher levels of innovative work behaviour (IWB), organizations such as Saudi Telecommunication Company (STC) must strengthen transformational leadership practices and promote effective knowledge sharing (KS). Transformational leadership plays a pivotal role in shaping employee behaviour by fostering creativity, adaptability, and innovation, which ultimately contributes to organizational effectiveness. This research contributes to the academic discourse by addressing existing theoretical gaps in the relationship between transformational leadership and innovative work behaviour (IWB), particularly through the mediating role of knowledge sharing (KS). It offers valuable insights for practitioners and policymakers seeking to drive innovation in knowledge intensive settings.